Occurrence of the Tamarix Leafhopper, Opsius stactogalus Fieber (Hemiptera: Cicadellidae), in Argentina - Virla, Eduardo Gabriel (2010)
The paleartic tamarix leafhopper,Opsius stactogalusFieber (Hemiptera: Cicadellidae), can reduce the growth of tamarisk due to the aggregate feeding imposed by their populations. The species was mentioned for Argentina in Metcalf´s catalogue (1967) without locality or region reference, and the contributions on Cicadellidae published by many authors after Metcalf omitted this distributional data. Populations of O. stactogalus on Tamarix sp. were found in 12 sites between 28º 48’ to 39º 17’ S and 64º 06’ to 70º 04’ W, located in both the Neotropical and Andean biogeographic regions.